Analisa Kelayakan Ekonomi Rumah Susun Sederhana Pekanabru - Arianti, Yesi; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Flat-house is one solution to fulfill the requirement of houses. It will increase with the increasing of human populations. The development of simple flat-house usually purposed for peoples with medium to low profit. Hire price must be considering of willingness to pay and ability to pay of that peoples. Purpose of this research is to investigate either proper or not the flat-house project built based on economic analysis so that it would be resulted a recommendation to the related institution. Indicators of proper investment were NPV (Net Present Value), BCR (Benefit Cost Ratio), IRR (Internal Rate of Retrun), BEP (Break Even Point) and sensitivity analysis. Calculation result of investment cost in this research which used method of approximate approach was Rp 22.315.717.450. The analysis result of proper investment for all parameter showed that the investment was proper to be continued because in the level of interest used was about 5,75% of proper investment, NPV value was positive, BCR value was above 1, IRR value was more than 5,75% (loading interest investment), and BEP was less than 25 years (project time). Key words: Analysis of proper investment, analysis of sensitivity, BCR, BEP, IRR, NPV